Possibilities and perspectives of bioflavonoids in treatment of eye diseases (Ukrainian Journal of Ophthalmology, 2026)
Possibilities and perspectives of bioflavonoids in treatment of eye diseases
Keywords: flavonoids; quercetin; hesperidin; diosmin; curcumin; diabetic retinopathy; cataract; glaucoma